Application of preventive medicine resources in the health insurance system - de Oliveira, Karla Regina Dias (Einstein (Sao Paulo), 2015)
OBJECTIVE: To identify the financial resources and investments provided for preventive medicine programs by health insurance companies of all kinds. METHODS: Data were collected from 30 large health insurance companies, with over 100 thousand individuals recorded, and registered at the Agência Nacional de Saúde Suplementar. RESULTS: It was possible to identify the percentage of participants of the programs in relation to the total number of beneficiaries of the health insurance companies, the prevention and promotion actions held in preventive medicine programs, the inclusion criteria for the programs, as well as the evaluation of human resources and organizational structure of the preventive medicine programs. CONCLUSION: Most of the respondents (46.7%) invested more than US$ 50,000.00 in preventive medicine program, while 26.7% invested more than US$ 500,000.00. The remaining, about 20%, invested less than US$ 50,000.00, and 3.3% did not report the value applied.